2010
DOI: 10.1002/chem.200903350
|View full text |Cite
|
Sign up to set email alerts
|

Adaptative Biaryl Phosphite–Oxazole and Phosphite–Thiazole Ligands for Asymmetric Ir‐Catalyzed Hydrogenation of Alkenes

Abstract: A library of readily available phosphite-oxazole/thiazole ligands (L1 a-g-L7 a-g) was applied in the Ir-catalyzed asymmetric hydrogenation of several largely unfunctionalized E- and Z-trisubstituted and 1,1-disubstituted terminal alkenes. The ability of the catalysts to transfer chiral information to the product could be tuned by choosing suitable ligand components (bridge length, the substituents in the heterocyclic ring and the alkyl backbone chain, the configuration of the ligand backbone, and the substitue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…92 High enantioselectivities (up to 92%) were obtained in the hydrogenation of several di-and trisubstituted enol phosphinates using this catalytic system however the enantioselectivities achieved do not surpass the values achieved with Ir-17b catalytic system.…”
Section: Enol Phosphinates and Enol Phosphonatesmentioning
confidence: 88%
See 2 more Smart Citations
“…92 High enantioselectivities (up to 92%) were obtained in the hydrogenation of several di-and trisubstituted enol phosphinates using this catalytic system however the enantioselectivities achieved do not surpass the values achieved with Ir-17b catalytic system.…”
Section: Enol Phosphinates and Enol Phosphonatesmentioning
confidence: 88%
“…Two types of N-donor group were studied, oxazole ( Figure 6, ligands 44) and thiazole ( Figure 6, ligands 45). 92 Phosphite-thiazole ligand 45a ( Figure 6) provided similar levels of enantioselectivity as those obtained with glucosamine-based Ir-23a catalytic system (Table 2, The previously mentioned phosphite-thioether ligands 57-60 ( Figure 7) were screened in the hydrogenation of several aryl/alkyl disubstituted substrates, including those containing a heteroaryl group. Again, furanoside ligand 58a provided the highest enantioselectivities (ee's up to 99%; Table 2, entries 27, 30, 50, and 60).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…We found that the ability of the catalysts to transfer chiral information to the product could be tuned by choosing suitable ligand components (bridge length, substituents in the heterocyclic ring and the alkyl backbone chain, the configuration of the ligand backbone, and the substituents/configurations in the biaryl phosphite moiety), so that enantioselectivities could be maximized for each substrate, as required. Enantioselectivities were therefore excellent ( ee values up to >99%) over a wide range of E ‐ and Z ‐trisubstituted and 1,1‐disubstituted terminal alkenes (Figure ) 15. It should be noted that these catalytic systems also had a high tolerance to the presence of a neighboring polar group, and therefore, tri‐ and disubstituted allylic alcohols S7 and S22 , acetates S8 , esters S6 , silanes S24 and S33 , and enol phosphinates S46 – S48 could be hydrogenated with high enantioselectivities ( ee values up to 99%).…”
Section: Application Of Phosphite–oxazole/thiazole Ligandsmentioning
confidence: 97%
“…Mixed phosphite–oxazoline/thiazoline ligands are exceptionally effective, providing better substrate versatility than earlier Ir–phosphinite/phosphine–oxazoline catalysts 12–14. Then our research has progressed to heterodonor biaryl phosphite, X‐ligands bearing more robust X‐donor groups than oxazolines (thiazoles,15 oxazoles,15 pyridines,16,17 and thioethers18–20). We have also performed mechanistic studies to explain the origin of enantioselectivity; this allows the rationalization of the modifications required of the ligand for improved selectivity 14b,19,20…”
Section: Introductionmentioning
confidence: 98%